En el nombre del otro: Cristianismo y pueblos originarios en la región chaqueña argentina (1965-1994) - Jouanny, Miguel Leone (Entre los libros de la buena memoria, 2022)
Pastoral Aborigen is a type of ecclesiastical indigenism with Christian roots and an ecumenical sense that, unlike other indigenist missions, did not seek to convert the indigenous people to Christianity, but rather to promote their development and contribute to their liberation. These missions were part of the conciliar renewal and were stressed between developmentalist precepts and leftist ideologies of the time.